IMPLEMENTASI KEBIJAKAN DANA DESA DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TETEAJI KECAMATAN TELLU LIMPOE KABUPATEN SIDENRENG RAPPANG - Mustanir, Ahmad (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
Implementation of the Village Fund and Community Participation in Development in Rural District of Tellu Limpoe Teteaji Sidenreng Rappang.The purpose of research is to determine the Village Fund Policy Implementation in Rural Development in the District Teteaji Tellu Limpoe Sidenreng Rappang and to determine the Community Participation in Rural Development in the District Teteaji Tellu Limpoe Sidenreng Rappang. The population of this study of 2,265 people, while the sample using the formula slovin is numbered 96 people.Techniques of data collection are (1) observation, (2) Interviews (3) of Library Studies and (4) questionnaire. The data was analyzed using frequency tables and percentages. The results of this study indicate that the Village Fund Policy Implementation indicator with a value of 69.78% both categories, Public Participation indicator with a value of 67.2% to the category of good, Rural Development Indicators in the District Teteaji Tellu Limpoe Sidenreng Rappang with a value of 71.4% categorized good.